Resistance of Cocoa to Black Pod Disease (Phytophthora palmivora Butl.) - . RUBIYO; WIDI AMARIA (Puslitbang Perkebunan, 2013)
The increase of cocoa production faces many problems such as black pod disease caused by Phytophthora palmivora. The disease may reduce the production of cocoa up to 44%. Control of the disease by chemical fungicides is costly and creates negative impact to humans and environment. Utilizing plant material which is resistant to black pod disease is an alternative to overcome this problem. It is also a long-term solution, which require information on the mechanism of cocoa resistance. Mechanism of plant resistance to diseases determined by structural and biochemical mechanism that work on the entire cycle of disease, both before penetration and after infection. Distribution activity of inoculum of P. palmivora in the disease cycle is influenced by the morphological characters of cocoa pod as a deposition of inoculum pre-penetration and inoculum penetration ability into the fruit tissue. Cocoa varieties in Indonesia resistant to black pod disease are ICCRI3, ICCRI 4, Sca 6, Sca 12 dan DRC 16. Key words: cocoa, mechanism of resistance, Phytophthora palmivora Butl.